Origin and chaotic propagation of multiple rotating detonation waves in hydrogen/air mixtures. (1st September 2020) - Zhao, Majie; Zhang, Huangwei
Abstract: The origin and chaotic propagation of multiple detonative waves in the two-dimensional modelled rotating detonation combustor fueled by premixed hydrogen/air mixtures are numerically investigated with detailed chemical mechanism. The discrete reactants inlets are adopted, to mimic the spatial non-uniformity of the propellant in the practical Rotating Detonation Engine (RDE) combustor. The emphasis is laid on the mechanism to induce the new detonation waves in the RDE and the influence of the reactant non-uniformity in RDE on the critical detonation combustion dynamics. The numerical experiments show that the stability and number of the rotating detonation wave are affected by the inlet total pressures and reactant equivalence ratios. The RDE with high inlet total pressure would experience chaotic instability before reaching stable propagation of detonation waves in near-stoichiometric mixtures, while for the RDE with low inlet total pressure, no chaotic propagation transient after the detonation initiation is observed. It is found that the chaotic propagation stage is responsible for the variation of the rotating detonative wave number and propagation direction. Frequent detonation extinction, re-ignition and re-orientation, irregular reactants refill zones, co-rotating and counter-rotating detonation waves are observed during chaotic stage. The explosive spots arising during this stage, which may initiate new detonation waves, result from the mutual enhancement between the travelling shock waves and the deflagrative fronts. Furthermore, the predictability of the chaotic detonation wave propagation is further confirmed in terms of the initial and boundary conditions, mesh and chemical mechanism. It is also found that the fuel equivalence ratio has a considerable impact on the number of the stabilized detonation wave and velocity deficit.